A Plea for the Newborn Diagnosis of Hb S-Hereditary Persistence of Fetal Hemoglobin. (4th May 2017) - Serjeant, Graham R.; Serjeant, Beryl E.; Hambleton, Ian R.; Oakley, Matthew; Thein, Swee Lay; Clark, Barnaby
Abstract: The gene for hereditary persistence of fetal hemoglobin (HPFH) in the Caribbean is much more common than previously estimated. To avoid labeling persons with the benign syndrome Hb S ( HBB : c.20A>T)/HPFH as a disease and wasting scarce resources, parental studies are recommended when newborn screening reveals a pattern consistent with an SS phenotype.